Enhancing wear resistance of AISI 304 alloy with shot peening and investigation of corrosion behaviour in marine water. (4th July 2021) - Çakir, F. H.; Öteyaka, M. Ö.; Er, Ü.; Bozkurt, F.
ABSTRACT: Austenitic stainless steels are widely used in many sectors, especially in the food processing and chemical sectors, due to their superior corrosion resistance and suitably safe contact with foodstuffs. In this study, AISI 304 alloy, which cannot be hardened by traditional heat treatment methods, was hardened with the shot-peening method. Characterisation studies of shot peened samples in different coverage (100%, 200%, 500%, and 1500%) have been carried out, and their wear resistance and corrosion resistance have been tested. It has been found that surface hardness and wear resistance increase after shot peening. However, the as-peened, and peened and polished samples undergo localised corrosion in a chloride environment, and the pits were more pronounced for the 200% coverage as-peened, and peened and polished samples. On the other hand, both samples exhibited semi-capacitive loop and Warburg corrosion impedance resistance. In general, the corrosion resistance was poor for as-peened samples compared to peened and polished samples, but the formation of the oxide layer was better. According to the results of this study, using shot peening as a surface hardening method is recommended with polishing to improve wear resistance and hardness of AISI 304 alloy.